ADIWIYATA SCHOOL MANAGEMENT IN SHAPING THE INDEPENDENCE OF ENVIRONMENTALLY CONSCIOUS STUDENTS IN ELEMENTARY SCHOOLS - Ria Adien; Yuniar Yuniar; Nurlaila Nurlaila; Zainal Berlian; Tutut Handayani (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to analyze the environmental management of Adiwiyata Schools in fostering students’ independence in waste management and environmental awareness at elementary schools throughout Penukal Abab Lematang Ilir Regency. The focus of the study includes the planning, implementation, and evaluation of school environmental management. This research employed a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, and documentation involving principals, Adiwiyata team members, teachers, and students. Data analysis was conducted through data reduction, data display, and conclusion drawing, with data validity ensured through source and technique triangulation. The findings indicate that environmental management planning was carried out through the formulation of environmentally oriented school policies, the integration of the Adiwiyata program into the curriculum, and the provision of supporting facilities and infrastructure. Program implementation was realized through habituation activities such as waste segregation, waste bank management, recycling activities, and active student involvement in maintaining the cleanliness of the school environment. Evaluation was conducted periodically to assess program effectiveness and the participation of the school community. This study concludes that systematically managed Adiwiyata School environmental management is capable of fostering students’ independence in waste management and enhancing their environmental awareness.